El invento bizantino de las minúsculas griegas frente a las unciales helenas tradicionales - Santana Henríquez, Germán (2016)
The invention of the Greek Byzantine minuscule against traditional Hellenic uncials».A fact that is often overlooked in the history of mankind is the invention of lowercase Greek letter in the ninth century AD during the Byzantine Empire. Until then, Greek texts were written in uncial or capital. Byzantine copyists turn all those works Greek antiquity had bequeathed to the West into this new point. Those texts which were not rendered into the new letter ended up being forgotten and irretrievably disappearing.Thus, both the records and the memory of a near or remote past depended highly on this new way of writing which became fashionable during the Middle Ages and found its way into the present day.
Un hecho que suele pasar desapercibido en la historia de la humanidad es la invención de la letra minúscula griega en el siglo ix de nuestra era durante el Imperio bizantino.Hasta entonces, todos los textos griegos estaban escritos en letra uncial o mayúscula;a partir de entonces los copistas bizantinos van a pasar a la nueva letra todas las obras que la Antigüedad griega había legado a Occidente. Todo lo que a partir de entonces no se pasó a la nueva letra quedó en el olvido o desapareció irremediablemente; por ello la memoria y el recuerdo del pasado basculó hacia esta nueva forma de escribir, que ha llegado hasta nuestros días.
Keywords: Lengua griega medieval; Arte bizantino; Escritura